WTX101 - an investigational drug for the treatment of Wilson disease - Weiss, Karl Heinz; Członkowska, Anna; Hedera, Peter; Ferenci, Peter (Expert opinion on investigational drugs, 2018)
INTRODUCTION: Wilson disease (WD) is a genetic disorder in which excess toxic copper accumulates in the liver, brain, and other tissues leading to severe and life-threatening symptoms. Copper overload can be assessed as non-ceruloplasmin-bound copper non-ceruloplasmin-bound copper (NCC) in blood. Current therapies are limited by efficacy, safety concerns, and multiple-daily dosing. Areas covered: This article reviews the literature on WTX101 (bis-choline tetrathiomolybdate), an oral first-in-class copper-protein-binding agent in development for the treatment of WD. Expert opinion: In a proof-of-concept phase II trial, once-daily WTX101 over 24 weeks rapidly lowered NCC levels and this was accompanied by improved neurological status without apparent initial drug-induced paradoxical worsening, reduced disability, stable liver function, with a favorable safety profile. WTX101 directly removes excess copper from intracellular hepatic copper stores and also forms an inert tripartite complex with copper and albumin in the circulation and promotes biliary copper excretion. These mechanisms may explain the rapid biochemical and clinical improvements observed. A phase III trial of WTX101 is ongoing and results are eagerly awaited to confirm if WTX101 can improve the treatment of this devastating disease.
Gesehen am 04.07.2019